Pain and fertility outcomes of nerve‐sparing, full‐thickness disk or segmental bowel resection for deep infiltrating endometriosis—A prospective cohort study. (16th September 2018) - Hudelist, Gernot; Aas‐Eng, Mee Kristine; Birsan, Tudor; Berger, Franz; Sevelda, Ursula; Kirchner, Lisa; Salama, Mohamad; Dauser, Bernhard
Abstract: Intoduction: Choosing the optimal treatment for bowel endometriosis, ie, conservative vs radical surgery, is under debate. We aimed to evaluate the surgical outcomes of segmental resection and disk resection regarding fertility, pain symptoms, and quality of life score of women with colorectal deep infiltrating endometriosis. Material and methods: From March 2011 to December 2016, 134 consecutive patients with symptomatic deep infiltrating endometriosis of the rectosigmoid up to 25 cm from the anal verge undergoing segmental resection or disk resection were prospectively evaluated regarding reduction in pain symptoms, fertility outcomes, and complication rates according to Clavien‐Dindo classification. Results: Of the 134 women included, segmental resection was performed in 102 (76.1%) women and disk resection was performed in 32 (23.9%) women. There was no difference in duration of surgery, complication rates, mean hospital stay, or discrepancy in hemoglobin level comparing the two groups. There was no significant difference regarding reduction of pain symptoms, fertility, and functional outcomes. One hundred and twelve (83.6%) women were followed up long‐term. In both cohorts, there was a significant reported decrease in pain symptoms and increase in quality of life scores. Of all the 61 infertile women, 26 (42.6%) became pregnant spontaneously, and 13 (21.3%) by in vitro fertilization with an overall pregnancy rate of 63.4%. The overall complication rate (Clavien‐Dindo III‐IV) was 8 of 134 (5.9%) without statistically significant difference between the cohorts. Conclusions: Both conservative surgery with disk resection, and nerve‐ and vessel‐sparing segmental resection reduce pain symptoms with equal morbidity. Fertility is improved with surgery with both techniques.